Metodologi Memahami Hadis - Benny Kurniawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Insitut Agama Islam Nahdlatul Ulama (IAINU) Kebumen, 2020)
The development of science from time to time has contributed to the emergence of new methods and approaches to understanding hadith, because hadith is one of the main sources of Islamic law, second only to the Al-Qur'an, cannot be separated from study and research. In the method of understanding (syarh) hadith, the scholars use 3 methods, namely the tahlili method (analytical), the ijmali method (global), and the muqarin method (comparison). Like an uncracked ivory, the three methods have their own strengths and weaknesses.